CUSTOMS SYSTEM: METHODOLOGICAL FUNDAMENTALS FOR DEFINITION OF THE CONCEPT - Кунєв, Юрій Дем'янович; Пивовар, Юрій Ігорович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose of the article is to develop theoretical provisions that will form the basis of a scientific-methodological approach to define the concept of a customs system. Research methods: hermeneutical method of cognition the essence of the system, legal analysis of customs legislation, methods of juxtaposition and comparison of the provisions of international and national customs legislation, as well as a method of generalization and modelization of new theoretical knowledge. The systematic approach to define the borders of the customs system and the further description of its elements became the basis of the methodology of this paper. Results: a customs system in its wide meaning is defined as a system formed by subsystems of customs legislation and customs legislation implementation; in the narrow sense it may be understood as a regulative and protective institute of a state for ensuring interaction of the national economy with the world economy, the world market and control over the cross-border flows of goods, vehicles, and individuals. Customs activity needs to set goals, look for issues and solve them at different levels of the customs system, namely: at the strategic level (issues that have been considered at the level of the customs system as a whole and at the level of formation of customs legislation attributes); at the tactical level (issues that have been considered at the level of customs activity implementation); at the operational level (issues that have been considered at the level of the implementation of customs business and compliance with customs legislation). According to these levels, it is necessary to have organizational models of activity at each level. It has been emphasized that at each level there are also tools which are crucial for a certain level of the customs system organization: a) for strategic they are represented by customs legislation; b) for tactical they are customs techniques, a customs procedure; c) for the operational level they are customs formalities. Discussion: it is argued that only a system-oriented concept of the customs system is capable to combine the activities that are organized by law that characterize this system. Such a system is an integral part of an economic system of a society (a state), so it must be considered a subsystem. In turn, indicators of the customs system can be considered a factor in the development of the economic system, since it affects both its indicators and structure. On separate grounds, it can be conditionally distinguished and considered as a separate one, for the investigation of its individual aspects regarding the organization of certain types of activity (legal, organizational, informational of customs activity or more narrowly that is customs business, etc.). The activity of customs legislation formation is difficult to separate from political activity in general and the formation of foreign economic activity.